Lifelong learning in Malaysia: Malaysian Higher Education Blueprint (MHEB) 2026-2035 - Hassan, Farihah; Laili, Normarliana; Ismail, Mohd Faiz; Abu Hasan, Norraidah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Malaysia is experiencing rapid technological, economic, and social changes driven by automation, AI, digitalisation, globalisation, and climate change. In response, the Malaysian Higher Education Blueprint (MHEB) 2026–2035 emphasizes lifelong learning as central to reform, redefining education as a continuous journey from childhood to adulthood, supported by businesses, communities, schools, and higher education institutions to foster a culture of ongoing learning.